Harmonic and interharmonic measurements through a compressed sampling approach. (January 2016) - Bonavolontà, Francesco; D'Apuzzo, Massimo; Liccardo, Annalisa; Miele, Gianfranco
Abstract: The paper deals with the distributed monitoring of harmonic and interharmonic pollution in electrical power delivery systems. In order to measure the disturbances and to identify the sources in a wide grid, a distributed measurement system with hundreds of measurement nodes has to be adopted. With the aim of obtaining the reduction of realization costs, the authors propose an innovative distributed architecture, based on cost-effective nodes, that takes advantage from the compressive sampling strategy. Differently from traditional approach, the network nodes will be only mandated to acquire and to digitize the line voltage directly in a compressed form, whereas a central measurement unit will receive data from all nodes deployed in the grid and will perform the successive signal reconstruction, making possible the use of low-performance hardware to realize them. The assessment of the compliance of the proposed measurement technique with the current power quality standards turns out to be mandatory, thus verifying the absence of artifacts introduced by the adopted compressed sampling approach.